Human papillomavirus infection in HIV-1 infected women in Catalonia (Spain): implications for prevention of cervical cancer. - Valeria Stuardo (Public Library of Science (PLoS), 2012)
Background High-risk human Papillomavirus infection is a necessary factor for cervical squamous intraepithelial lesions and invasive cervical cancer. In HIV-1-infected women, HPV infection is more prevalent and a higher risk of cervical cancer has been identified. We aimed to calculate the prevalence of infection by HR-HPV, determine the factors associated with this infection and abnormal cytology findings and to describe the history of cervical cancer screening in HIV-1-infected women. Methods We enrolled 479 HIV-1-infected women from the PISCIS cohort. Each patient underwent a gynecological check-up, PAP smear, HPV AND Hybrid capture, HPV genotyping, and colposcopy and biopsy, if necessary. We applied questionnaires to obtain information on sociodemographic, behavioral, clinical, and cervical screening variables. We present a cross-sectional analysis. Results Median age was 42 years. The prevalence of HR-HPV infection was 33.2% and that of high-grade squamous intraepithelial lesions (HSIL) was 3.8%. The most common genotypes were 16(23%), 53(20.3%), and 52(16.2%). The factor associated with HR-HPV infection was age <30 years (odds ratio[OR],2.5; 95%confidence interval[CI],1.1-5.6). The factors associated with the presence of HSIL or low-grade squamous intraepithelial lesions (LSIL) were CD4T-lymphocyte count <200 cells/mm(3) versus >500 cells/mm(3) (OR,8.4; 95%CI,3.7-19.2), HIV-1 viral load >10,000 copies/mL versus <400 copies/mL (OR,2.1; 95%CI,1.0-4.4), and use of oral contraceptives (OR,2.0; 95%CI,1.0-3.9). Sixty percent of HIV-1-infected women had had one Pap smear within the last 2 years. Conclusions The high prevalence of HPV infection and cervical lesions in the HIV-1-infected population in Catalonia, as well as the low coverage and frequency of screening in this group, means that better preventive efforts are necessary and should include vaccination against HPV, better accessibility to screening programs, training of health care professionals, and specific health education for HIV-1-infected women.